An Exploratory Study of Agression in School-Age Children: Underlying Factors and Implications for Treatment - Priddis, Lynn; Landy, Sarah; Moroney, Darren; Kane, Robert (Australian Academic Press Pty Ltd, 2014)
Aggressive behaviour in school-aged children presents a significant challenge for society. If not managed, it can result in adverse academic, social, emotional, and behavioural outcomes for the child. In addition, it can create stress for families and become a significant burden for the community as these children reach adolescence and adulthood, and engage in antisocial behaviours. Using a three-step exploratory analytical strategy, this study explored parent and child reports of a diverse range of underlying developmental and clinical variables that have been identified in the literature as predictors of aggressive child behaviour, and which could be addressed within an Australian school or community context. A total of 57 children and their parents were recruited from a referral-based Western Australian child mental health service, and the wider community. A group of 31 clinically aggressive children were identified and compared to a group of 26 non-aggressive children. The aggressive group was reported as having a greater prevalence of internalising symptoms, including anxiety and depression, and their aggressive behaviour was more likely to be of the callous/unemotional type, relative to their non-aggressive counterparts. Significant predictors of belonging to the aggressive group included child social problems, thought problems, attention problems, affective problems, narcissism, symptoms of ADHD and PTS, and low maternal self-esteem. Findings are presented and discussed in the context of established theories. Recommendations for principles of treatment for aggressive children and their families are suggested.